Revisiting Afghanistan's Drug Policy: A Policy Analysis of Eradication, Harm Reduction, and Economic Dependencies - Mohammad Qais Azizi; Mohammad Faisal Wardak; Edris Afzali; Ali Rahimi; Jerico Bautista Ogaya; Enayatollah Ejaz; Basir Ahmad Hasin; Mohammad Masudi; Don Eliseo Lucero‐Prisno III (Health Science Reports)
ABSTRACT Background Afghanistan's responses to illicit drugs have oscillated between punitive eradication and limited harm‐reduction initiatives. Two decades of heavy external spending, entrenched conflict, and an economy intertwined with opium have blunted policy effectiveness. Methods Guided by Walt and Gilson's policy‐triangle, we undertook a document‐based review (2001–2024). Twenty‐seven national laws, strategies, and analytical reports were retrieved from government and multilateral repositories. Data were coded thematically using Braun‐and‐Clarke's six‐phase approach to map policy content, actors, context, and implementation barriers. Results Four themes emerged. First, Afghan drug policy has passed through distinct phases—post‐2001 tolerance, eradication campaigns, a harm‐reduction window, and the current Afghan government's prohibition—each shaped by shifting political economies. Second, a complex actor constellation spans ministries, insurgent groups, multilateral donors, and opium‐dependent farming communities, often with conflicting incentives. Third, implementation is hampered by corruption, chronic insecurity, rural poverty, and a shrinking treatment infrastructure (113 centres for an estimated 1.5 million users in 2024). Fourth, persisting failures fuel cycles of addiction, rural impoverishment, and insurgent financing, while recent poppy bans have accelerated a pivot to methamphetamine production. Conclusion Sustainable progress demands moving beyond short‐term enforcement toward an integrated rural‐development and public‐health agenda. Priorities include: (i) secure livelihood alternatives for farmers; (ii) restoration and scale‐up of evidence‐based treatment and harm‐reduction services; (iii) transparent governance mechanisms that engage local communities. A balanced, context‐sensitive policy mix offers the best prospect of reducing drug‐related harm while addressing the structural drivers that have long frustrated Afghan counter‐narcotics efforts.